Independent Use of Jenga Game Among Indonesian EFL Learners: Student Engagement, Ability, and Motivation - Nastiti, Inaka Trisna; Safriyani, Rizka; Anifaturrohmaniah (ICONELT, 2024)
This study examines the independent utilization of the Jenga game, also referred to as Building Blocks, as a learning medium to improve the motivation, engagement, and ability of Indonesian EFL learners to express their opinions in English. This research offers a comprehensive comprehension of the experiences and perspectives of students when Jenga is integrated into the English language learning process through a case study approach. Twenty-eight eighth-grade students from Class VIII F at MTsN 1 Sidoarjo participated in the study from February to May 2024. Classroom observations and questionnaires were implemented to ascertain students’ engagement, confidence, and capacity to express their thoughts in English. The results indicated that integrating Jenga into educational activities substantially improved students’ confidence in expressing their opinions, reduced anxiety, and increased active participation. The game’s interactive nature nurtured a collaborative environment, encouraging peer learning and motivation. Students exhibited a greater propensity to participate in class discussions and honed their critical thinking and communication abilities. The study emphasizes the efficacy of gamified learning aids in fostering linguistic abilities and fostering confidence in EFL contexts. These findings indicate that Jenga is a valuable resource for educators interested in innovative methods to support language acquisition and create a dynamic and motivating classroom environment. This method emphasizes the potential of games to promote active learning and real-world language use.